Increased polyunsaturated fatty acid levels in muscles and offal organs of sheep fed commercial concentrates - Goh, Yong Meng; Rajion, Mohamed Ali; M. N., Noor Hayati; Idrus, Zulkifi; Ng, C. F. (Veterinary Association Malaysia, 2003)
A study was carried out to determine the effectiveness of feeding a commercially available concentrate to sheep to increase the polyunsaturated fatty acids (PUFAs) in their tissues. Sixteen Malin crossbred sheep with an average age of two years old were used for this trial. The sheep were allocated into two equal groups of eight animals each and fed either concentrate (CONC) or Digitaria setivalva grass (GRAS) was fed for five weeks inclusive of a week of adaptation period. The animals were slaughtered upon termination of the trial, and concentrations of the n-3 and n-6 PUFAs were measured in the biceps femoris and longissimus dorsi muscles, liver, heart and kidneys. The concentrations of linoleic acid and n-6 PUFAs in the liver, heart and kidneys were consistently higher (p<0.05) in animals fed concentrate only compared to grass-fed sheep. The higher concentrations oflinoleic acid and n-6 PUFAs corresponded to the high amounts of these fatty acids in the concentrate diet. The linolenic acid content of tissues from the animals fed grass only was consistently higher (p<0.05) than those fed concentrate only. However, the total n-3 PUFA concentrations were not different in most tissues across treatments, except in the liver and heart tissues of the GRAS sheep where they were higher compared to CONC animals. The results indicate that a relatively short period offour weeks is sufficient to enrich sheep tissues with n-6 PUFAs through intensive concentrate feeding. The findings are particularly valuable when employed in the pre-slaughter fattening stage of sheep to produce PUFA -enriched healthy mutton.